Tourism and community capacity building : a literature review. - Aref, Fariborz; Redzun, Ma'arof (2008)
Tourism as an industry is increasing rapidly in developing countries. Tourism is simultaneously portrayed as a destroyer of culture, undermining social norms and economies, degrading social structures, stripping communities of individuality and as a savior of the poor and disadvantaged, providing opportunities and economic benefits, promoting social exchange and enhancing livelihoods. The purpose of this study is to explore the concept of community capacity building with respect to tourism development. I discuss how the processes of community capacities (individual, organizational and community) and community empowerment draw from and contribute to the physical, social and human capital essential to community based tourism. In this way, I review literature on community capacity building and discuss the related concepts of community capacities, community empowerment and community participation, with particular attention to how they may apply to community based tourism. The literature included in this review, draws from experience in a variety of disciplines, namely community psychology, personnel management, natural resource management, sociology and international development.